„Sprawy korzenne”. Fenomenologia Zuzanny Ginczanki - Wojda, Dorota (Przestrzenie Teorii, 2018)
The paper concerns Zuzanna Ginczanka’s floristic signatures (trees, flowers and fruits), which are used by the poet to construct literary tropes. It shows how, by means of these signatures, the following oppositions are introduced: life/death, surface/depth, outside/inside, form/substance, phenomenon/essence. The crux of the argument is that in Ginczanka’s poetry there is a conflict concerning the value of phenomenology, i.e. what is really important: the phenomena (trees, flowers, fruits) or the hidden essences („the Questions of Root”)? I go on to argue that the poet’s thinking corresponds to Maurice Merleau-Ponty’s philosophy, in which the subject’s experience is considered to be related to his life environment and the philosophy of the body is identified with the phenomenology of perception. Emphasizing „the Questions of Root” in the very title of the paper indicates what is most problematic for Ginczanka and, at the same time, what determines her recognition of poetry as an expression of unattainable desires.